2021 23rd International Conference on Control Systems and Computer Science (CSCS) 2021
DOI: 10.1109/cscs52396.2021.00065
|View full text |Cite
|
Sign up to set email alerts
|

Monitor Indoor Air Quality to Assess the Risk of COVID-19 Transmission

Abstract: The year 2020 will remain in the memory of all mankind as the year of the COVID-19 pandemic. The pandemic has affected the world economy, caused more than a million deaths in 2020 alone, changed the way people work and learn and, last but not least, changed the way people interact in society. Social distancing, along with wearing a face mask, is the best solution to prevent the spread of COVID-19 virus. What happens when in certain spaces social distance is difficult and can be accidentally violated without in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Learning activities in educational buildings, such as classrooms were primarily observed as part of the monitoring system ( 27 , 28 , 30 , 31 , 39 , 62 , 65 ). The prevention of SARS-CoV-2 transmission inside such infrastructures and the safe reopening of some public spaces and educational facilities were implemented through mechanical or non-mechanical means.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Learning activities in educational buildings, such as classrooms were primarily observed as part of the monitoring system ( 27 , 28 , 30 , 31 , 39 , 62 , 65 ). The prevention of SARS-CoV-2 transmission inside such infrastructures and the safe reopening of some public spaces and educational facilities were implemented through mechanical or non-mechanical means.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, CO 2 monitors are available in the marketplace and moreover, the Federation of European Heating, Ventilation and Air Conditioning Associations (REHVA) recommends installing CO 2 sensors to alert against poor ventilation in indoor areas ( 27 ). Eleven of the fifty four conducted studies examined the use of sensors ( 31 , 35 , 36 , 39 , 43 , 44 , 49 , 53 , 56 , 62 , 63 , 65 , 66 ), and indicated that the NDIR sensor is the simplest and most common technology ( 8 , 15 ). The mechanism of the NDIR sensor is to evaluate the value of light that is absorbed across wavelengths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As indoor life accounted for the majority of daily routine during COVID-19 pandemic, indoor pollution has received considerable attention in research [ 26 , 27 ]. Numerous previous studies have shown that indoor pollutant concentrations are more dominant than those outdoors [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%